Unveiling the Gap: Exploring Gender Inequality in Economic Empowerment Across India - Veena, R. Senthamizh (International Journal of Humanities and Education Development (IJHED), 2024)
Gender inequality in economic empowerment remains a pervasive issue across the globe, manifesting in various forms such as unequal pay, limited access to economic resources, and disparities in employment opportunities and career advancement. This systemic imbalance stifles not only individual potential but also hampers overall economic growth and development. While this inequality exists universally, it is particularly pronounced in Indian society, rooted in deeply embedded cultural norms and historical gender roles. Traditionally, women's subordinate position has deprived them of asset ownership and participation in financial decision-making. Additionally, they have been denied employment opportunities and face discrimination in the labor market. These factors have led to a significant gender gap in economic participation at both household and societal levels. In this context, this study attempts to examine the gender inequality in economic empowerment in India through the lens of asset ownership, wage disparity, and labor force participation. This study is based on secondary data taken from the reports of the National Family Health Survey and the Periodic Labour Force Survey of the Government of India. The study found that, the female labour force participation rate was 46.2 per cent less than the male labour force participation rate and on an average, women earned Rs. 136.32 less than men in daily wage earnings. The study concludes that addressing gender inequality in economic empowerment requires a comprehensive approach at the policy, organizational, and societal level, including implementing and enforcing gender-sensitive labor laws, promoting equal pay for equal work, and providing affordable childcare and parental leave to level the playing field.